The Growth Hormone Level of Bali Cattle’s Post Treatment with Ethinil Esthradiol and Progesteron Hormones in Combination with Mineral - Mandala, Aletha Yuliana; Suwiti, Ni Ketut; Suardana, I Wayan (Journal of Veterinary and Animal Sciences; Vol 2 No 1 (2019)DO - 10.24843/JVAS.2019.v02.i01.p01, 2019)
This study aims to find out the growth hormone level of bali cattle’s post giving of ethinyl estradiol and progesterone hormones combined with mineral. The total sample of 64 bali cattle is divided into 4: Group I (Control) is not given hormone ethinyl estradiol, progesterone and mineral. Group II is given the hormone ethinyl estradiol and progesterone, without mineral. Group III was not given ethinyl estradiol and progesterone hormones, with mineral administration. Group IV is given hormone ethinyl estradiol, progesterone and mineral. At the end of the study, measurements were performed to determine the growth hormone level using ELISA method. The data of the research were analyzed by the analysis of variance. The result showed that male cattle growth hormone (268.281±73.13pg/ml) was higher than females (236.250±13.79pg/ml). The growth hormone level of young cattle was higher (264.94±74.42pg/ml) than adult (239.59±14.05pg/ml). Level of growth hormone of bali cattle with highest minerals(266.97±74.15pg/ml) compared without minerals (237.56±11.05pg/ml). The growth hormone level of bali cattle with higher levels of ethinyl estradiol and progesterone hormone (263.31±74.81pg/ml) compared with no ethinyl estradiol and progesterone hormone (241.22±18.8pg/ml). The results are age and sex effect on growth hormone level with hormone ethinyl estradiol and progesterone combined with mineral. Giving ethinyl estradiol and progesterone hormones combined with significant mineral (P<0.05) may increase the growth hormone level of young male bali cattle.